Mudharabah Financing Stagnation in Rural Islamic Microfinance: Stagnasi Pembiayaan Mudharabah di Keuangan Mikro Syariah Pedesaan - Mohammad Firmansyah; Moh.Jeweherul Kalamiyah; Khairul Anam (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Mudharabah financing is conceptually positioned as a core partnership-based instrument in Islamic finance emphasizing fairness and risk sharing. Specific Background: However, its implementation in rural Islamic Microfinance Institutions remains limited, particularly in agricultural communities of Sukowono and Jambesari Darus Sholah. Knowledge Gap: Prior studies largely focus on user perception and preference, with limited exploration of operational implementation gaps between regulatory frameworks and rural economic realities. Aims: This study aims to analyze factors causing the failure of DSN-MUI Fatwa No. 7 of 2000 implementation in mudharabah financing among rural farmers. Results: Using a qualitative case study with triangulation, findings reveal zero customer uptake for nearly six years, driven by three main barriers: functional literacy gap, institutional rigidity, and dominance of informal finance. The study also identifies a “Risk Mitigation Paradox,” where strict procedures intended to reduce risk instead restrict access, alongside “Subsistence Mismatch,” reflecting misalignment between productive financing design and consumptive household needs. Novelty: This research introduces analytical concepts including Functional Literacy Gap, Risk Mitigation Paradox, and Subsistence Mismatch to explain systemic stagnation. Implications: The findings suggest the need for simplified procedures, participatory financial literacy, and hybrid financing integrating social and commercial instruments to restore relevance of mudharabah in rural economic empowerment. Highlights• Zero adoption of profit-sharing scheme recorded over six years• Administrative rigidity creates exclusion despite compliance intentions• Informal lenders dominate due to faster access and simpler procedures KeywordsMudharabah Financing; Islamic Microfinance Institutions; Rural Farmers; Financial Literacy; Informal Economy